Cytomegalovirus immediate-early 1 proteins form a structurally distinct protein class with adaptations determining cross-species barriers - Schweininger, Johannes; Scherer, Myriam; Rothemund, Franziska; Schilling, Eva-Maria; Worz, Sonja; Stamminger, Thomas; Muller, Yves (PLoS Pathogens, 2021)
Author summary Cytomegaloviruses have evolved in very close association with their hosts resulting in a highly species-specific replication. Cell-intrinsic proteins, known as restriction factors, constitute important barriers for cross-species infection of viruses. All cytomegaloviruses characterized so far express an abundant immediate-early protein, termed IE1, that binds to the cellular restriction factor promyelocytic leukemia protein (PML) and antagonizes its repressive activity on viral gene expression. Here, we present the crystal structures of the PML-binding domains of rat and human cytomegalovirus IE1. Despite low amino-acid sequence identity both proteins share a highly similar and unique fold forming a distinct protein class. Functional characterization revealed a common mechanism of PML antagonization. However, we also detected that the respective IE1 proteins only interact with PML proteins of the natural host species. Interestingly, expression of HCMV IE1 allows rat cytomegalovirus infection in human cells. This indicates that the cellular restriction factor PML forms an important barrier for cross-species infection of cytomegaloviruses that might be overcome by adaptation of IE1 protein function. Our data suggest that the cytomegalovirus IE1 structure represents an evolutionary optimized protein fold targeting PML proteins via coiled-coil interactions.
CRIS-Team WoS Importer:2021-08-27

Exploring the Human Cytomegalovirus Core Nuclear Egress Complex as a Novel Antiviral Target: A New Type of Small Molecule Inhibitors - Alkhashrom, Sewar; Kicuntod, Jintawee; Häge, Sigrun; Schweininger, Johannes; Muller, Yves; Lischka, Peter; Marschall, Manfred; Eichler, Jutta (Viruses, 2021)
Nuclear egress is an essential process in the replication of human cytomegalovirus (HCMV), as it enables the migration of newly formed viral capsids from the nucleus into the cytoplasm. Inhibition of the HCMV core nuclear egress complex (core NEC), composed of viral proteins pUL50 and pUL53, has been proposed as a potential new target for the treatment of HCMV infection and disease. Here, we present a new type of small molecule inhibitors of HCMV core NEC formation, which inhibit the pUL50-pUL53 interaction at nanomolar concentrations. These inhibitors, i.e., verteporfin and merbromin, were identified through the screening of the Prestwick Chemical Library® of approved drug compounds. The inhibitory effect of merbromin is both compound- and target-specific, as no inhibition was seen for other mercury-organic compounds. Furthermore, merbromin does not inhibit an unrelated protein-protein interaction either. More importantly, merbromin was found to inhibit HCMV infection of cells in three different assays, as well as to disrupt HCMV NEC nuclear rim formation. Thus, while not being an ideal drug candidate by itself, merbromin may serve as a blueprint for small molecules with high HCMV core NEC inhibitory potential, as candidates for novel anti-herpesviral drugs.
CRIS-Team Scopus Importer:2021-04-16
Keywords: antiviral activity; core NEC inhibitor; human cytomegalovirus; nuclear egress complex (NEC); small molecule inhibitor

Nuclear Egress Complexes of HCMV and Other Herpesviruses: Solving the Puzzle of Sequence Coevolution, Conserved Structures and Subfamily-Spanning Binding Properties - Marschall, Manfred; Häge, Sigrun; Conrad, Marcus; Alkhashrom, Sewar; Kicuntod, Jintawee; Schweininger, Johannes; Kriegel, Mark; Loesing, Josephine; Tillmanns, Julia; Neipel, Frank; Eichler, Jutta; Muller, Yves; et al. (Viruses, 2020)
Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric nuclear egress complex (core NEC). These core NECs serve as hexameric lattice-structured platforms for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina as well as membrane-rearranging functions (multicomponent NEC). The regulation of nuclear egress has been profoundly analyzed for murine and human cytomegaloviruses (CMVs) on a mechanistic basis, followed by the description of core NEC crystal structures, first for HCMV, then HSV-1, PRV and EBV. Interestingly, the highly conserved structural domains of these proteins stand in contrast to a very limited sequence conservation of the key amino acids within core NEC-binding interfaces. Even more surprising, although a high functional consistency was found when regarding the basic role of NECs in nuclear egress, a clear specification was identified regarding the limited, subfamily-spanning binding properties of core NEC pairs and NEC multicomponent proteins. This review summarizes the evolving picture of the relationship between sequence coevolution, structural conservation and properties of NEC interaction, comparing HCMV to alpha-, beta- and gamma-herpesviruses. Since NECs represent substantially important elements of herpesviral replication that are considered as drug-accessible targets, their putative translational use for antiviral strategies is discussed.
CRIS-Team WoS Importer:2020-08-07

The crystal structure of the varicella-zoster Orf24-Orf27 nuclear egress complex spotlights multiple determinants of herpesvirus subfamily specificity - Schweininger, Johannes; Kriegel, Mark; Häge, Sigrun; Conrad, Marcus; Alkhashrom, Sewar; Lösing, Josephine; Weiler, Sigrid; Tillmanns, Julia; Egerer-Sieber, Claudia; Decker, Andrea; Rovis, Tihana Lenac; Eichler, Jutta; et al. (Journal of Biological Chemistry, 2022)
Varicella-zoster virus (VZV) is a human pathogen from the α-subfamily of herpesviruses. The VZV Orf24-Orf27 complex represents the essential viral core nuclear egress complex (NEC) that orchestrates the egress of the preassembled virus capsids from the nucleus. While previous studies have primarily emphasized that the architecture of core NEC complexes is highly conserved among herpesviruses, the present report focuses on subfamily-specific structural and functional features that help explain the differences in the autologous versus nonautologous interaction patterns observed for NEC formation across herpesviruses. Here, we describe the crystal structure of the Orf24-Orf27 complex at 2.1 Å resolution. Coimmunoprecipitation and confocal imaging data show that Orf24-Orf27 complex formation displays some promiscuity in a herpesvirus subfamily-restricted manner. At the same time, analysis of thermodynamic parameters of NEC formation of three prototypical α-, β-, and γ herpesviruses, i.e., VZV, human cytomegalovirus (HCMV), and Epstein-Barr virus (EBV), revealed highly similar binding affinities for the autologous interaction with specific differences in enthalpy and entropy. Computational alanine scanning, structural comparisons, and mutational data highlight intermolecular interactions shared among α-herpesviruses that are clearly distinct from those seen in β- and γ-herpesviruses, including a salt bridge formed between Orf24-Arg167 and Orf27-Asp126. This interaction is located outside of the hook-into-groove interface and contributes significantly to the free energy of complex formation. Combined, these data explain distinct properties of specificity and permissivity so far observed in herpesviral NEC interactions. These findings will prove valuable in attempting to target multiple herpesvirus core NECs with selective or broadacting drug candidates.
CRIS-Team Scopus Importer:2022-03-04

The human cytomegalovirus IE1 protein antagonizes PML nuclear body-mediated intrinsic immunity via the inhibition of PML de novo SUMOylation - Schilling, Eva-Maria; Scherer, Myriam; Reuter, Nina; Schweininger, Johannes; Muller, Yves; Stamminger, Thomas (Journal of Virology, 2017)
PML nuclear bodies (NBs) are accumulations of cellular proteins embedded in a scaffold-like structure built by SUMO-modified PML/TRIM19. PML and other NB proteins act as cellular restriction factors against human cytomegalovirus (HCMV); however, this intrinsic defense is counteracted by the immediate early protein 1 (IE1) of HCMV. IE1 directly interacts with the PML coiled-coil domain via its globular core region and disrupts NB foci by inducing a loss of PML SUMOylation. Here, we demonstrate that IE1 acts via abrogating the de novo SUMOylation of PML. In order to overcome reversible SUMOylation dynamics, we made use of a cell-based assay that combines inducible IE1 expression with a SUMO mutant resistant to SUMO proteases. Interestingly, we observed that IE1 expression did not affect preSUMOylated PML; however, it clearly prevented de novo SUMO conjugation. Consistent results were obtained by in vitro SUMOylation assays, demonstrating that IE1 alone is sufficient for this effect. Furthermore, IE1 acts in a selective manner, since K160 was identified as the main target lysine. This is strengthened by the fact that IE1 also prevents AsO-mediated hyperSUMOylation of K160, thereby blocking PML degradation. Since IE1 did not interfere with coiled-coil-mediated PML dimerization, we propose that IE1 affects PML autoSUMOylation either by directly abrogating PML E3 ligase function or by preventing access to SUMO sites. Thus, our data suggest a novel mechanism for how a viral protein counteracts a cellular restriction factor by selectively preventing the de novo SUMOylation at specific lysine residues without affecting global protein SUMOylation.
EVALuna2:33771
Keywords: Human cytomegalovirus; Immediate early 1; Intrinsic immunity; Nuclear domain 10; PML nuclear bodies; Sumoylation